Перспективи застосування процедури мічення риб в іхтіологічних дослідженнях та природоохоронній роботі в Україні - Khudyi, Oleksii; Hoch, Inna; Khudyi, Oleksandr (Факт, 2021)
The article provides an overview of various methods of marking and tagging fish, the purpose, and features of their use in ichthyological research and conservation practice, including an ichthyological and aquaculture practice in Ukraine. Much attention is paid to the advantages and disadvantages of different approaches, which is useful for researchers to correctly choose the relevant method. As an important case, the release of 10000 individuals sterlet (A. ruthenus) on June 22, 2021, by WWF Ukraine and partners in the Ukrainian part of the Danube River, is described. 1012 sterlet youngsters were marked by VIE marks (visible implant elastomer marks). After the release, based on this approach the very first try of sterlet youngsters monitoring will be launched.
The use of fish marking and tagging procedures as a promising approach in ichthyological research and conservation work in Ukraine
Keywords: риби, мітки, бирки